IMPLEMENTASI WEB SERVICE PADA POINT OF SALE SUPERMARKET (Information Technology and Telematics, 2015)
AbstracA  developing technology  information  has  made information  spread  easily.  Especially  information  in  sector health. A lot of Online information that demand everyone to be uptodate. One of Them that easily we can get is Website. Now with the existence of website about system information point of sale, someone can easily get any information that he / she needs. That information will be very usefull for cashier in supermarket.In this case, we can get information through Web Service. The implementation  of Web  Service will  easily  the  staff  to  get information. Information will be displayed  with Json format, because  the  datas  that  displayed  are  recapitulation  of  the transactions  from  that  supermarket,  which  are  the  data transaction per day, data transaction per week, data transaction from cashier, data Product that consumen bought and data total transaction that every cashier did.Key Word : web service, json